Trends of Ocean Acidification and pCO2 in the Northern North Sea, 2003–2015. Issue 10 (29th October 2019) - Omar, A. M.; Thomas, H.; Olsen, A.; Becker, M.; Skjelvan, I.; Reverdin, G.
Abstract: For continental shelf regions, the long‐term trend in sea surface carbon dioxide (CO2 ) partial pressure ( p CO2 ) and rates of ocean acidification are not accurately known. Here, we investigate the decadal trend of observed wintertime p CO2 as well as computed wintertime pH and aragonite saturation state (Ωar ) in the northern North Sea, using the first decade long monthly underway data from a voluntary observing ship covering the period 2004–2015. We also evaluate how seawater CO2 chemistry, in response to physical and biological processes, drives variations in the above parameters on seasonal and interannual timescales. In the northern North Sea, p CO2, pH, and Ωar are subject to strong seasonal variations with mean wintertime values of 375 ± 11 μatm, 8.17 ± 0.01, and 1.96 ± 0.05. Dissolved inorganic carbon is found to be the primary driver of both seasonal and interannual changes while total alkalinity and sea surface temperature have secondary effects that reduce the changes produced by dissolved inorganic carbon. Average interannual variations during winter are around 3%, 0.1%, and 2% for p CO2, pH, and Ωar, respectively and slightly larger in the eastern part of the study area (Skagerrak region) than in the western part (North Atlantic Water region). Statistically significant long‐term trends were found only in the North Atlantic Water region with mean annual rates of 2.39 ± 0.58 μatm/year, −0.0024 ± 0.001 year ‐1, and −0.010 ± 0.003 year ‐1 for p CO2, pH, and Ωar, respectively. The drivers of the observed trends as well as reasons for the lack of statistically significant trends in the Skagerrak region are discussed. Plain Language Summary: Temperate and high latitude marine shelf areas are generally net sinks of atmospheric carbon dioxide (CO2 ), and they are experiencing ocean acidification. Decadal trends in the magnitude of the sinks and acidification occurring in these regions are not accurately known mainly due to limited time series and higher natural spatiotemporal variability compared to open oceans. Hence, an important question is whether the surface seawater CO2 growth and acidification on the shelves can be predicted from atmospheric CO2 increase as is the case for the open oceans? To contribute to the answer of this question, we compiled the first decade‐long, monthly time series of surface seawater CO2 and acidification parameters in the northern North Sea (2004–2015). Our analyses confirm that the area is a year‐round CO2 sink and further demonstrate its strong seasonal and interannual variations. In the western parts of the study area, we found wintertime trends that are statistically significant and similar to what is expected from atmospheric CO2 increase and observed in the open ocean. In the eastern parts, seasonal and interannual changes were somewhat stronger, but wintertime trends were weaker and not statistically significant. Key Points: The study area is a year‐round CO2 sink with strong seasonal and spatial variations DIC is the primary driver of variability in p CO2 and ocean acidification variables while SST and TA have couteracting secondary influences In the western region, rates of p CO2 growth and acidification over the last decade closely tracked the atmospheric CO2 increase